The Values of Moral Education in the Book of Bulughul Maram: Study of Adab Hadiths - Vikri Aflaha Qomari; Romlah Abubakar Askar; Abdul Ghofur (al-Afkar, Journal For Islamic Studies, 2026)
Moral education in Islam plays a crucial role in shaping students' character. Morality is a core teaching in Islam, and the Hadith is a key source for shaping students' moral values. Therefore, this study aims to examine the values of moral education in the Bulughul Maram book: a study of adab hadiths. This study employs a qualitative library research method. The findings demonstrate that Ibn Hajar views morality as a condition firmly embedded in a person, giving rise to an action, and good deeds stemming from commendable morality are called adab. Therefore, special treatment is needed for parents and educators to instill commendable morality in students. Ultimately, instilling moral values in students will have implications for their morality. This study aims to provide significant insights and contributions to the field of Islamic education.